Abstract Models and Cognitive Mismatch in Formal Verification - Rukšėnas, Rimvydas; Curzon, Paul (Electronic Communications of the EASST, 2011)
We present ongoing work to accommodate fine-grained analysis of interactive systems via model checking. We argue that this can be achieved by combining a basic abstract model of user behaviour and a separate constraint on the acceptable degree of cognitive mismatch. To explain the problem and illustrate our approach, we present a simple scenario related to number entry in infusion pumps.